Seasonal and Spatial Changes in FDOM Compositions in the Continental Shelf Area of the East China Sea. Issue 5 (20th October 2019) - Bai, Ying; Cui, Zhengguo; Su, Rongguo; Qu, Keming
Abstract: The components, sources, and seasonal and spatial changes of fluorescent dissolved organic matter (FDOM) in the continental shelf area of the East China Sea (ECS), were determined by excitation and emission matrices (EEM) spectroscopy and parallel factor analysis (PARAFAC). The PARAFAC model identified four FDOM components from 234 samples in June and October 2014. The four components consisted of three terrestrial humic-like components (C1, C2, and C3) and one tryptophan-like component (C4). Based on the spatial and seasonal distributions, as well as their correlations with salinity, chlorophyll a (chl a ), and apparent oxygen utilization, the following assignments were made: C1, C2, and C3 originated mainly from terrestrial inputs and could also be affected by phytoplankton and microbial activity; C4 was a result of allochthonous and autochthonous sources and was a biologically labile component. In most of the study area, the fluorescence intensities of FDOM were higher in June than in October. Terrestrial inputs, anthropogenic activity, and autochthonous sources could affect the seasonal and spatial variations of FDOM. Allochthonous sources were the main factors influencing FDOM in the continental shelf area of the ECS. The higher fluorescence index and lower humification index in June demonstrated that FDOM had increased autochthonous production and a lower degree of humification. The effect of photodegradation was also stronger in June.